Relationship between fluency and reading comprehension in 4th and 5th grade students - Guaresi, Ronei (2018)
Based on theoretical psycholinguistic assumptions regarding the cognitive processing of reading, including and especially through the Bottom-up and Top-Down and Double-Rota models, and also in literature review studies on the relationship between verbal fluency and reading comprehension, this study aims to evaluate the relationship between reading comprehension and reading fluency. The reading fluency was evaluated through the grapheme-phoneme conversion time criterion and comprehension by means of reading to answer open-ended questions. In this study, of an elementary public school in the countryside of Bahia, we observed a strong negative correlation between the two variables studied (r = - 0.70), because the higher the reading comprehension, the less time taken to read. We observe what the speed was relevant for comprehension until the conversion between 5 and 6 graphemes per second. It seems that the lack of automatic recognition of graphemes imposes a higher cost of cognitive processing, that is, processing by phonological and ascending pathways seems to consume the essentially limited range of cognitive resources of working memory. Consequently, there are no cognitive resources for access to meaning. We conjectured that the lateness of converting graphemes into phonemes, as we have seen in this study, indicates that serial processing and preferential use of the phonological route and the ascending path do not contribute to parallel processing and comprehension.